2021
DOI: 10.1371/journal.pone.0260837
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TCF4 repeat expansion length in corneal endothelium and leukocytes of patients with Fuchs endothelial corneal dystrophy

Abstract: Expansion of CTG trinucleotide repeats (TNR) in the transcription factor 4 (TCF4) gene is highly associated with Fuchs Endothelial Corneal Dystrophy (FECD). Due to limitations in the availability of DNA from diseased corneal endothelium, sizing of CTG repeats in FECD patients has typically been determined using DNA samples isolated from peripheral blood leukocytes. However, it is non-feasible to extract enough DNA from surgically isolated FECD corneal endothelial tissue to determine repeat length based on curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this study, we examined ungenotyped FECD patient surgical samples and utilized a variety of primary and immortalized cell culture models from FECD patients with pathological expansions of trinucleotide repeats in intron 3 of the TCF4 gene (the most common genotype that causes a late onset of disease) to characterize lipid peroxidation and key iron metabolites in FECD and determine whether ferroptosis plays a role in its pathogenesis (46)(47)(48).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examined ungenotyped FECD patient surgical samples and utilized a variety of primary and immortalized cell culture models from FECD patients with pathological expansions of trinucleotide repeats in intron 3 of the TCF4 gene (the most common genotype that causes a late onset of disease) to characterize lipid peroxidation and key iron metabolites in FECD and determine whether ferroptosis plays a role in its pathogenesis (46)(47)(48).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that both FECD genetic background and UVA increase CEC susceptibility to nonapoptotic oxidative cell death and lipid peroxidation through the accumulation of toxic intracellular concentrations of ferrous iron. To test this hypothesis, we studied ungenotyped FECD patient surgical samples and immortalized and primary cell culture models from FECD patients with pathological expansions of trinucleotide repeats in intron 3 of the TCF4 gene (the most common genotype associated with FECD (49)(50)(51)) and evaluated for increases in lipid peroxidation, cytosolic Fe 2+ , and susceptibility to ferroptosis attributable to genetic background and UVA exposure.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously utilised a long-read amplification-free sequencing method to determine that expanded copies of CTG18.1 (defined as ≥50 repeats) are somatically unstable in peripheral blood leukocytes, with inherited repeat lengths positively correlating with increased CTG18.1 instability (Hafford-Tear et al 2019). Southern blot data of FECD patient-derived corneal endothelial cell cultures have also suggested that CTG18.1 repeat length is greater in affected cells compared to leukocytes, in keeping with the dogma that STRs typically display high levels of instability within affected cell types (Wieben et al 2021;Depienne and Mandel 2021). For example, in myotonic dystrophy type 1, the diseaseassociated repeat has been reported to expand up to 4,000 repeats in skeletal muscle, representing up to a 25-fold increase in length compared to blood (Nakamori et al 2013).…”
Section: Introductionmentioning
confidence: 74%
“…However, results from one recent study that used long read sequencing of the RNA isolated from FECD corneal endothelium suggest that the TCF4 repeat expansion in corneal endothelium is much larger than in peripheral leukocytes of patients. 42 We hypothesize that cells with larger repeat lengths may be more prone to foci formation.…”
Section: Discussionmentioning
confidence: 98%